Analysis of Heavy Metal Mercury (Hg) Content in Nile Tilapia (Oreochromis niloticus) from Rawa Taliwang Lake West Sumbawa - Seftiyani, Ditayara; Khairuddin, Khairuddin; Kusmiyati, Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Rawa Taliwang Lake is a place where various types of aquatic organisms (macroorganisms and microorganisms) occur biological processes. Industrial activities can lead to the emergence of pollutants that contaminate the environment, including air, land, and water, if industrial waste is not managed properly. Surface water, especially in lakes, is easily polluted by heavy metals such as mercury (Hg). Mercury (Hg) levels that exceed normal limits in fish can be an indicator of environmental pollution. The study aims to determine the levels of heavy metal mercury (Hg) in tilapia (Oreochromis niloticus) and to assess the safety of consuming the fish. Samples were analyzed using the Atomic Absorption Spectroscopy (AAS) method. The results showed that tilapia samples had mercury (Hg) levels of 0.1 mg/kg (ppm), but were still safe for consumption. In line with BPOM Number 9 of 2022 which sets the threshold for heavy metal mercury (Hg) contamination in processed food products at 0.50 mg/kg.